2020
DOI: 10.1016/j.reseneeco.2020.101149
|View full text |Cite
|
Sign up to set email alerts
|

Competing eco-labels and product market competition

Abstract: I analyze a green product market in which eco-labeling programs compete-programs certifying the environmental quality of the product to their respective standards. Specifically, I examine the strategic competition between an industry-sponsored program and a program sponsored by nongovernmental organization (NGO) in a duopoly product market where eco-labels are strategic variables for firms. In particular, I analyze the eects of such eco-label competition on environmental benefit and social welfare. I show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Fourth, the result of this study shows that eco-labeling information does not influence green attitude awareness on young consumers but it directly increases green purchase intention. It confirms Hosseinikhah Choshaly (2019) and Li (2020) in that eco-labeling positively influences consumers in making decision to choose green products and informing the consumers on how the products are made.…”
Section: Discussionsupporting
confidence: 63%
“…Fourth, the result of this study shows that eco-labeling information does not influence green attitude awareness on young consumers but it directly increases green purchase intention. It confirms Hosseinikhah Choshaly (2019) and Li (2020) in that eco-labeling positively influences consumers in making decision to choose green products and informing the consumers on how the products are made.…”
Section: Discussionsupporting
confidence: 63%
“…A good example is eye drops, as there are several different names on the market with the same active substance. • Eco-labeling-generally, its use improves consumer choice and awareness, finally improving social welfare (Li 2020). Until today, eco-labeling has not been used by any certification organization.…”
Section: Prescription and Sales Of Pharmaceuticalsmentioning
confidence: 99%
“…Li [66] analyzed the eco-labeling competition issue theoretically through a dynamic Bertrand duopoly in which two eco-labeling programs (sponsored by the industry or by an environmental NGO) compete strategically in setting the ecolabel features. The author found that competition between the programs may lead to the same high environmental benefits in comparison to when only the NGO program exists, and that competition may yield a higher social welfare.…”
Section: Discussionmentioning
confidence: 99%